2017
DOI: 10.1017/s0021859617000715
|View full text |Cite
|
Sign up to set email alerts
|

Differences in skeletal muscle proteolysis in Nellore and Angus cattle might be driven by Calpastatin activity and not the abundance of Calpain/Calpastatin

Abstract: SUMMARYThe present study aimed to explore the molecular factors underlying differences in Calpain/Calpastatin proteolytic system in Nellore and Angus cattle. Longissimus muscle samples were collected in Nellore (n = 6; body weight (BW) = 373 ± 37·3 kg) and Angus (n = 6; BW = 383 ± 23·9 kg) cattle at slaughter for analysis of gene and protein expression, and Calpastatin enzyme activity. Additionally, the myofibrillar fragmentation index was used to quantify the extension of proteolysis in longissimus muscle sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
5
0
4
Order By: Relevance
“…In addition, Moloto et al (2017) emphasized that the complexity of the tenderness process and the different metabolic pathways involved in muscle-to-meat transformation lead to the difficulty of identifying markers for meat tenderness. Moreover, Martins et al (2017) assessing the proteolysis of Angus and Nelore cattle, observed that the higher proteolysis in longissimus muscle of Angus compared to Nelore cattle was not caused by differences in the expression of genes that encoding calpastatin or calpain, nor due to the abundance of these enzymes, but due to the higher calpastatin activity in skeletal muscle of Nelore compared to Angus animals. Therefore, our study indicate that differences found in shear force values between genetic groups involve others complex systems and only the gene expression from calpain-calpastatin proteolytic system is not able to reply our results.…”
Section: Gene Expressionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, Moloto et al (2017) emphasized that the complexity of the tenderness process and the different metabolic pathways involved in muscle-to-meat transformation lead to the difficulty of identifying markers for meat tenderness. Moreover, Martins et al (2017) assessing the proteolysis of Angus and Nelore cattle, observed that the higher proteolysis in longissimus muscle of Angus compared to Nelore cattle was not caused by differences in the expression of genes that encoding calpastatin or calpain, nor due to the abundance of these enzymes, but due to the higher calpastatin activity in skeletal muscle of Nelore compared to Angus animals. Therefore, our study indicate that differences found in shear force values between genetic groups involve others complex systems and only the gene expression from calpain-calpastatin proteolytic system is not able to reply our results.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Sabe-se que Bos indicus apresentam maior atividade de calpastatina quando comparados aos Bos taurus. Essa atividade elevada de calpastatina em bovinos Bos indicus diminui a proteólise post mortem, afetando negativamente a maciez KOOHMARAIE, 1994;PRINGLE et al, , 1999MARTINS et al, 2017;. No entanto, a diferença na proteólise post mortem entre essas subespécies não tem sido associada apenas ao sistema calpaína-calpastatina, como também a outros sistemas proteolíticos e até mesmo a expressão gênica e abundância proteica de marcadores de maciez da carne (OUALI et al, 2006).…”
Section: Maciez E Proteóliseunclassified
See 3 more Smart Citations